Principles of information security - Whitman, Michael E.; Mattord, Herbert J. (Cengage, 2022)
Introduce the latest trends, developments and technology within information security today with Whitman/Mattord's market-leading Principles of Information Security, 7th Edition. Designed specifically for information systems students, this edition's balanced focus addresses all aspects of information security, beyond simply a technical control perspective. A broad overview of the entire field explores important terms and examines how to manage an effective information security program. A new module details incident response and detection strategies. In addition, relevant updates highlight the latest practices with expanded coverage of security operations, emerging legislative issues, information management toolsets, digital forensics and the most recent policies and guidelines that correspond to federal and international standards. MindTap digital resources offer interactive content to further strength an understanding of information security for successful business decision-makers.